2022
DOI: 10.1007/s11136-022-03217-9
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life of children born very preterm: a multinational European cohort study

Abstract: Purpose This study aims to (1) describe the health-related quality of life (HRQoL) outcomes experienced by children born very preterm (28–31 weeks’ gestation) and extremely preterm (< 28 weeks’ gestation) at five years of age and (2) explore the mediation effects of bronchopulmonary dysplasia (BPD) and severe non-respiratory neonatal morbidity on those outcomes. Methods This investigation was based on data for 3687 children born at < 32 weeks’ gestat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 59 publications
4
8
1
Order By: Relevance
“…A study of EP-born children from 11 European countries revealed that HRQoL was particularly impaired both by BPD as well as by other severe non-respiratory morbidities. 15 We also observed a correlation between poorer HRQoL and the administration of postnatal steroids. However, it is important to bear in mind that neonates treated with postnatal steroids constitute a particularly vulnerable group who require steroids to facilitate weaning from ventilatory support, and therefore are at heightened risk of adverse outcomes, that is bias by indication is probably at play here.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…A study of EP-born children from 11 European countries revealed that HRQoL was particularly impaired both by BPD as well as by other severe non-respiratory morbidities. 15 We also observed a correlation between poorer HRQoL and the administration of postnatal steroids. However, it is important to bear in mind that neonates treated with postnatal steroids constitute a particularly vulnerable group who require steroids to facilitate weaning from ventilatory support, and therefore are at heightened risk of adverse outcomes, that is bias by indication is probably at play here.…”
Section: Discussionsupporting
confidence: 51%
“…Bronchopulmonary dysplasia (BPD) and intraventricular haemorrhage (IVH) were associated with poorer physical health in early adulthood in a Swedish VLBW cohort. 14 A recent article by Kim et al 15 reported lower HRQoL in very preterm children with BPD and severe non-respiratory morbidity. Moreover, EP-born children from our 91-92 cohort, who received neonatal steroids scored lower in the domain for role/social functioning at 10 years of age.…”
mentioning
confidence: 98%
“…Various studies approve of this trend; however, absolute morbidity and mortality rate at the earliest gestational age is variable (Lee et al, 2020;Rysavy et al, 2020). Extremely preterm infants are at increased risk of developing sepsis, necrotizing enterocolitis, also retinopathy of prematurity, intraventricular hemorrhage, bronchopulmonary dysplasia, and white matter damage (Kim et al, 2023). This poses a significant challenge for neonatologists.…”
Section: Introductionmentioning
confidence: 99%
“…This poses a significant challenge for neonatologists. According to research, the premature birth rate in developed countries like UK, Greece, Turkey, and Germany was 73%, 75%, 69%, and 63%, respectively (Kim et al, 2023). Such infants' survival rate has significantly improved over the last twenty years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation